"Mixed Media": An Example of Pablo Picasso's Combination of Non-Artist's Paints with Tube Colors from the Menil Collection. Issue 3 (August 2013) - Hanspach-Bernal, Ellen; Bezur, Anikó
Abstract : Pablo Picasso created the painting Femme au chapeau assise sur une chaise (Seated woman with a hat) in Mougins, France, on September 10, 1938. He gave form to the painting's figure by adhering coarse-grained sand to the primary wood panel support. He then applied color to the composition using fluid and glossy paints. The swirling of colors at interfaces resembles the appearance of marbled paper, which suggests that the paint colors were applied in close succession. The relatively fast drying of the paint may be inferred from the retention of discrete boundaries between the wisps of different colors. Colors applied at a later stage appear to be level with earlier ones, indicating that Picasso added them while the latter were still fluid. In situ XRF analysis of the various colors indicates that some contain colorants uncharacteristic of house paints. Though analysis of the white, blue, and black areas did not allow their positive identification as Ripolin paint colors, their pigment components are consistent with contemporary formulation of non-artist's paints. Picasso may have taken and applied these three colors from "can to canvas, " while he manipulated artist's tube paints to achieve the handling properties he desired.